1992
DOI: 10.1128/jvi.66.7.4399-4406.1992
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the murine cytomegalovirus glycoprotein B gene and its expression by recombinant vaccinia virus

Abstract: The gene encoding glycoprotein B (gB) of murine cytomegalovirus (MCMV) strain Smith was identified, sequenced, and expressed by recombinant vaccinia virus. The gB gene was found adjacent to the polymerase gene, as it is in the genome of human cytomegalovirus (HCMV). The open reading frame consists of 2,784 nucleotides capable of encoding a protein of 928 amino acids. Comparison with gB homologs of other herpesviruses revealed a high degree of homology. The similarity between the MCMV gB and the HCMV gB is most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 38 publications
1
27
1
Order By: Relevance
“…Because this sequence does not encompass a splice donor motif (23), we concluded that insufficient stability of the heteroduplexes due to AT-rich sequences around the poly(A) signal (Fig. 2) resulted in overdigestion of the DNA-RNA hybrids (25). Thus, the exact 3Ј end of the BHV-1 UL6 and UL7 mRNAs remains to be determined, as does the corresponding poly(A) addition site for HSV-1 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Because this sequence does not encompass a splice donor motif (23), we concluded that insufficient stability of the heteroduplexes due to AT-rich sequences around the poly(A) signal (Fig. 2) resulted in overdigestion of the DNA-RNA hybrids (25). Thus, the exact 3Ј end of the BHV-1 UL6 and UL7 mRNAs remains to be determined, as does the corresponding poly(A) addition site for HSV-1 (24).…”
Section: Discussionmentioning
confidence: 99%
“…As a source of viral antigens, lysates of infected MEF were prepared 24 h after infection after a 4-h period of metabolic labeling with [3SS]methionine in the late phase of viral gene expression. Lysates from CV-1 cells were made 7 h after infection with vaccinia virus wild-type strain Copenhagen or with the vaccinia virus recombinant Vac-gB which expresses the gB gene of murine CMV (15). Procedures for biosyn-thetical labeling, preparation of cell lysates, and the immunoprecipitation as well as the protein separation on SDS-polyacrylamide (7.5%) gels were done as described previously (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…Strict species specificity has hindered the study of human CMV (HCMV) in animals, and infection of mice with murine CMV (MCMV) has been used extensively as a model for studying the pathogenesis of CMV infection (8,34,46,57). The human and murine viruses are biologically similar in replication and pathogenesis (25,45) and have homologous genomes (52), which display similar genetic organizations and encode analogous gene products with similar functions (19,31,43,44,50,51,68). The genomes of HCMV and MCMV are linear, double-stranded DNA molecules approximately 230 kb in length and encode more than 200 genes (10,52), many of which are arranged collinearly on the HCMV and MCMV genomes.…”
mentioning
confidence: 99%